Recording the optimistic. An audiovisual approach to the city of Lisbon by its architecture school in the 1980s - Silva, L. M. (2016)
With the revolution of 25 April 1974, Portugal initiated a unique cultural journey that paralleled, in the architectural field, the questioning of the modern movement that occurred since the aftermath of World War II. The academic context was a particular mirror for this criticism. The director of the Lisbon architecture course pronounced its engagement in “a sort of counter-culture”; the cultural critique that occurred, however, was more of a fortunate accident. In fact, an optimistic post-traumatic euphoria was a common element in some of the most radical pedagogical expressions that took place. In the face of the ‘creative’ productions that unfolded under the Lisbon architecture school in the 1980s, we acknowledge an unconventional form of expression that leads us to question whether a particular identity frame has characterised Portuguese architectural culture and its interrelation with the city of Lisbon ever since. This paper provides evidence for such a claim by examining previously untapped primary sources – testimonies and documents – that relate directly to Lisbon’s architecture course between 1976 and 1986 and which have informed background research for a PhD. Three videos from the School’s archives were analysed to demonstrate how students related to the topic of urbanity, specifically that of Lisbon, via this particular form of art.